2017
DOI: 10.1016/j.gore.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal based treatment of ovarian anaplastic ependymoma with anastrozole

Abstract: ObjectiveOvarian anaplastic ependymoma is a rare gynecologic malignancy that poses diagnostic and treatment challenges. Treatment of sub-optimally debulked disease usually portends poor prognosis. Molecular testing of tumor specimen can identify more specific targets for additional therapy such as estrogen and progesterone receptors (ER/PR).CaseA 29-year-old woman presented with incidental finding of large bilateral adnexal masses and elevated CA 125. Biopsy proved anaplastic ovarian ependymoma with high ER/PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, the International Menopause Society statement does not mention whether ependymoma is a contradiction for hormone replacement therapy or not 10. Strong positive staining results were observed for ER and PR receptors, in reported cases 4,9. Our patient was administered hormone replacement therapy because of serious peri-menopausal syndrome, and her staining results revealed slightly positive ER and moderately positive PR receptors.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the International Menopause Society statement does not mention whether ependymoma is a contradiction for hormone replacement therapy or not 10. Strong positive staining results were observed for ER and PR receptors, in reported cases 4,9. Our patient was administered hormone replacement therapy because of serious peri-menopausal syndrome, and her staining results revealed slightly positive ER and moderately positive PR receptors.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, authors suggested that ER replacement therapy after castration stimulates viable malignant ependymal cells to proliferate, and that antiestrogens such as tamoxifen can be used postoperatively 8. Furthermore, some studies have demonstrated antiestrogens’ role in the treatment of ovarian or pelvic ependymoma 4,9. However, the International Menopause Society statement does not mention whether ependymoma is a contradiction for hormone replacement therapy or not 10.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Positivity for both ER and PR enables treatment with hormonal therapies such as aromatase inhibitors. [11] Our patient received hormonal therapy and has disease-free survival at 8 months postoperatively.…”
Section: Figure 2: (A) True Ependymal Rosette (H and E ×40) (B) Tumor Cells With Fibrillary Processes Inset: "Salt-pepper" Nuclear Chromamentioning
confidence: 82%
“…Gorski et al reported a patient with advanced ovarian ependymoma who underwent sub-optimal surgical debulking followed by adjuvant chemotherapy with BEP, which resulted in a partial response. Due to extensive residual tumour tissues, the patient was maintained on anastrozole for over fifteen months without increased tumour burden [ 16 ]. Hence, high levels of oestrogen during pregnancy may stimulate viable malignant ependymal cells to proliferate.…”
Section: Discussionmentioning
confidence: 99%